Implementation of multidisciplinary care reduces maternal mortality in women with sickle cell disease living in low‐resource setting. Issue 9 (9th June 2017) - Asare, Eugenia Vicky; Olayemi, Edeghonghon; Boafor, Theodore; Dei‐Adomakoh, Yvonne; Mensah, Enoch; Ghansah, Harriet; Osei‐Bonsu, Yvonne; Crabbe, Selina; Musah, Latif; Hayfron‐Benjamin, Charles; Covert, Brittany; Kassim, Adetola A.; et al.
Abstract: Sickle cell disease (SCD) is associated with adverse pregnancy outcome. In women with SCD living in low‐resource settings, pregnancy is associated with significantly increased maternal and perinatal mortality rates. We tested the hypothesis that implementing a multidisciplinary obstetric and hematology care team in a low‐resource setting would significantly reduce maternal and perinatal mortality rates. We conducted a before‐and‐after study, at the Korle‐Bu Teaching Hospital in Accra, Ghana, to evaluate the effect of a multidisciplinary obstetric‐hematology care team for women with SCD in a combined SCD‐Obstetric Clinic. The pre‐intervention period was assessed through a retrospective chart review to identify every death and the post‐intervention period was assessed prospectively. Interventions consisted of joint obstetrician and hematologist outpatient and acute inpatient reviews, close maternal and fetal surveillance, and simple protocols for management of acute chest syndrome and acute pain episodes. Primary outcomes included maternal and perinatal mortality rates before and after the study period. A total of 158 and 90 pregnant women with SCD were evaluated in the pre‐ and post‐ intervention periods, respectively. The maternal mortality rate decreased from 10 791 per 100 000 live births at pre‐intervention to 1176 per 100 000 at post‐intervention, representing a risk reduction of 89.1% ( P = 0.007). Perinatal mortality decreased from 60.8 per 1000 total births at pre‐intervention to 23.0 per 1000 at post‐intervention, representing a risk reduction of 62.2% ( P = 0.20). A multidisciplinary obstetric and hematology team approach can dramatically reduce maternal and perinatal mortality in a low‐resource setting.